A smartphone-assisted hybrid sensor for simultaneous potentiometric and distance-based detection of electrolytes - Phoonsawat, Kamonchanok; Agir, Ismail; Dungchai, Wijitar; Ozer, Tugba; Henry, Charles S. (ELSEVIER, 2022)
At home electrolyte analysis is of growing interest due to the importance for early diagnosis for various diseases. This work presents the first device that integrates a potentiometric ion-selective electrode (ISE) with distance -based colorimetric detection for the simultaneous analysis of K+ and Cl(- )ions at the point of care (POC). This hybrid sensing device was designed in a two-dimensional configuration using a plastic transparency sheet containing a stencil printed K+-ISE and a paper substrate for distance-based colorimetric detection of Cl-. K+ quantification was performed using a low-cost (<$25) lab-made Wi-Fi supported potentiometer with a custom smartphone application while Cl- ions were quantified with an instrument-free distance-based paper analytical device (dPAD). The total analysis time is 5 min once the sample is added. The K+-ISE showed a sensitivity of 55.89 +/- 2.52 mV/decade from 0.1 to 100 mM with a limit of detection (LOD) of 0.01 mM. The linear working range for Cl- detection was 0.5-50 mM whereas the LOD was 0.16 +/- 0.05 mM. The proof-of-concept application of the sensing hybrid device was demonstrated in human urine and artificial sweat samples containing K+ and Cl- ions at physiologically relevant ranges. The recoveries were found to be 88-108% for K+ and 90-104% for Cl(-)showing the potential use of the proposed device for low-cost routine analysis of biological samples at POC.
Keywords: Distance -based paper device; Colorimetric detection; Potentiometric ion -selective electrode; Chloride; Potassium; Point-of-care; SELECTIVE ELECTRODES; QUANTIFICATION; DEVICE; CARBON; IONS; ACID; Chemistry